2020
DOI: 10.1002/jso.25859
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of tumor mutation burden in hepatocellular carcinoma after radical hepatectomy

Abstract: Background and Aim This study aimed to assess the potential relationship between tumor mutation burden (TMB) and the recurrence risk of hepatocellular cancer (HCC) after curative resection and tried to develop a reliable TMB based nomogram. Methods This retrospective study was conducted in 128 patients (40 patients suffered from a recurrence of HCC) who had received radical hepatectomy by the same surgical team. A nomogram model was constructed using the R and EmpowerStats software. Results TMB was not associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Therefore, the high mutation frequency of genes is associated with improved immunotherapy responses, long-lasting clinical benefits, and progression-free survival ( Rizvi et al, 2015 ). In 2020, Cai et al (2020) reported that higher mutation frequency was closely associated with the poorer clinical outcomes of patients with hepatocellular carcinoma. Likewise, our data indicated that patients with PAAD in the high-risk subgroup with high gene mutation frequency had worse prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high mutation frequency of genes is associated with improved immunotherapy responses, long-lasting clinical benefits, and progression-free survival ( Rizvi et al, 2015 ). In 2020, Cai et al (2020) reported that higher mutation frequency was closely associated with the poorer clinical outcomes of patients with hepatocellular carcinoma. Likewise, our data indicated that patients with PAAD in the high-risk subgroup with high gene mutation frequency had worse prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, with the help of X-title software analysis, we found that when the TMB = 4.2 was used as the boundary between a high and low TMB, the difference in prognosis between the two groups was the greatest. HCC patients with high TMB had a poor prognosis, and these results are consistent with the conclusion of Cai et al (2020). More interestingly, TMB = 4.2 was used as a cutoff, and the highand low-TMB groups exhibited an obvious difference regarding immune cell infiltration.…”
Section: Discussionsupporting
confidence: 84%
“…Owada-Ozaki et al from Japan found that higher TMB was correlated with shorter disease-free survival in NSCLC patients [33]. A study from China demonstrated that in HCC patients who had received radical resection, patients with higher TMB tend to have higher recurrence risk rate, and it was an independent risk factors of RFS [34]. We identi ed the median number of TMB in iCCAs was 1.25 (range 0.03-54.74).…”
Section: Tp53 Rbm10 Kras and Ipo5mentioning
confidence: 86%